Structuring Private Sustainability Governance: Combining Rule-Based and Goal-Based Mechanisms - Daniel Wörner; Niklas Letmathe; Marin Jovanovic; Thomas Friedli (Journal of Business Ethics, 2025)
This study investigates the structuring of private sustainability governance as a critical mechanism for facilitating sustainability transitions. Drawing on 33 semi-structured interviews with manufacturing firms, regulatory bodies, policy associations, auditing firms, and management consultancies, the study examines how firms navigate increasing external governance pressures, including regulatory ambiguity, compliance demands, market expectations, and stakeholder accountability, while simultaneously managing internal governance through organizational restructuring, sustainable performance measurement, data management, human resources, and incentive structures. The findings highlight the importance of integrating rule-based and goal-based private sustainability governance through two key mechanisms: shaping external governance by aligning with and influencing regulatory standards, and adapting internal governance to embed sustainability into core business operations. This study develops a hybrid governance framework that demonstrates how firms leverage both mechanisms in parallel, revealing the tensions inherent in balancing regulatory compliance with strategic sustainability ambitions. We make a further contribution by underscoring the role of ethical change management in fostering transparency, accountability, and proactive sustainability commitments. By examining governance structures in combination with ethical considerations, the study advances the discourse on private sustainability governance, offering both theoretical insights and practical implications for firms navigating the transition toward sustainable systems.
Keywords: 300; Private sustainability governance; Sustainable systems; Rule-based governance; Goal-based governance